Comportamento de plantas de arroz híbrido em função da qualidade fisiológica das sementes - Mielezrski, Fabio (2008)
The work had the objective of evaluating the behavior of populations of hybrid rice plants which were cultivated isolated, and the individual behavior and plants originated from seeds of high and low vigor of hybrid rice, inside of populations that were constituted of different combinations of seed line distributions. The experiment was conducted in the didactic experimental area of the agronomy school. It was used seeds of hybrid rice of the cultivar Avaxi, which belongs to the Ricetec®, including two types characterized as low and high vigor. Two studies were conducted. On the first, the effect of seed vigor on isolated plants, cultivated in hollows of 50 cm of depth, was evaluated. Two treatments were tested; plants originated from low and high vigor seeds, being each parcel composed by only one plant. On the second study, the evaluation was on the individual behavior of plants inside a population, as long as the entire population behavior established with different systems of distribution of plants originated from high and low vigor seeds, on the seed line. The experiment had 5 different combinations of seed line distribution of the plants originated from high and low vigor seeds, in seed lines of 4 meters of length. The plants were obtained by sowing each lot in distinct treys with soil as subtract, in a depth of 2,5cm with later transplant of the emerged plants to the field. It was concluded that plants of hybrid rice originated from seeds of high vigor shows better performance than the plants originated from low vigor seeds inside of a population. Increases at the ratio of plants originated from high vigor seeds, at the establishment of a population of hybrid rice plants, provide increases on the population yield and yield components. Hybrid rice populations established with high vigor seeds presents grain yield over 30%. Although presenting a superior performance, the plants originated from high vigor seeds don´t exert dominance effects on the plants originated from low vigor seeds.